Spiroconyone A, a new phytosterol with a spiro [5, 6] ring system from Conyza japonica. Issue 27 (7th May 2020) - Xiao, Long-Gao; Zhang, Yu; Zhang, Hong-Li; Li, Ding; Gu, Qiong; Tang, Gui-Hua; Yu, Qian; An, Lin-Kun
Abstract : The first rearranged phytosterol (spiroconyone A) with an unusual spiro [5, 6] ring system and two new TDP1 inhibitors 7 and 10 showing a strong synergistic effect with topotecan were isolated from Conyza japonica . Abstract : Spiroconyone A (1 ), the first rearranged phytosterol featuring an unusual spiro [5, 6] ring system, and nine known compounds (2–10 ) were isolated from the aerial parts of Conyza japonica . The structure of 1 was elucidated through spectroscopic methods, and its absolute configuration was determined by single-crystal X-ray diffraction analysis. Enzyme-based assay revealed that spiroconyone A showed weak TDP1 inhibition and compounds 7 and 10 showed TDP1 inhibition with IC50 values of 36 μM and 16 μM, respectively. MTT assay indicated that 7 and 10 showed a strong synergistic effect with the clinical TOP1 inhibitor topotecan in MCF-7 cells. Compound 5 displayed the most potent cytotoxicity against MCF-7 cells with a GI50 value of 3.3 μM. Furthermore, a hypothetical biosynthetic pathway for 1 was proposed. This work provides valuable information that the secondary metabolites from Conyza japonica could be developed as anticancer agents.